Título Padrão: a contribuição dos estudos de usuários para o desenvolvimento da competência informacional infantil - Aguiar, Niliane Cunha de; Gomes, Marcos Aurélio (Informação em Pauta, 2021)
The children's universe has been the object of study through specific methodologies in several fields, including Education, Psychology and Marketing. However, there is a lack of studies in the area of ​​Information Science and, consequently, in Librarianship. In this way, the work now attempted, by means of bibliographic survey and bibliometric study, to demonstrate the need for reflection on the best practices for conducting studies with children in information units. The results of the bibliometric analysis carried out in the BRAPCI database highlights the absence of work in the area of ​​Information Science on the subject, demonstrating the relevance of new research that develop practices capable of discovering the informational needs of children, favoring the creation of new products and information services in children's and school libraries to develop children's information competence.